Reduced NLRP3 Gene Expression Limits the IL-1β Cleavage via Inflammasome in Monocytes from Severely Injured Trauma Patients - Shinwan Kany; Johann-Philipp Horstmann; Ramona Sturm; Katharina Mörs; Borna Relja (Mediators of Inflammation)
Objective. Traumatic injury or severe surgery leads to a profound immune response with a diminished functionality of monocytes and subsequently their IL-1β release. IL-1β plays an important role in host immunity and protection against infections. Its biological activation via IL-1β-precursor processing requires the transcription of inflammasome components and their activation. Deregulated activity of NOD-like receptor inflammasomes (NLR) like NLRP3 that leads to the maturation of IL-1β has been described in various diseases. While the role of other inflammasomes has been studied in monocytes, nothing is known about NLRP3 inflammasome after a traumatic injury. Here, the role of the NLRP3 inflammasome in impaired monocyte functionality after a traumatic injury was analyzed. Measurements and Main Results. Ex vivo-in vitro stimulation of isolated CD14+ monocytes with lipopolysaccharide (LPS) showed a significantly higher IL-1β secretion in healthy volunteers (HV) compared to trauma patients (TP) after admission. Reduced IL-1β secretion was paralleled by significantly lowered gene expression of NLRP3 in monocytes from TP compared to those of HV. Transfection of monocytes with NLRP3-encoding plasmid recovered the functionality of monocytes from TP regarding the IL-1β secretion. Conclusions. This study demonstrates that CD14+ monocytes from TP are significantly diminished in their function and that the presence of NLRP3 components is necessary in recovering the ability of monocytes to produce active IL-1β. This recovery of the NLRP3 inflammasome in monocytes may imply a new target for treatment and therapy of immune suppression after severe injury.